+0  
 
0
23
1
avatar+96 

Factor 2x^2 + 5x + 3 = 0

Olpers  Aug 27, 2018

Best Answer 

 #1
avatar+343 
+3

\(2x^2 + 5x + 3 = 0\) factors to \((2x+3)(x+1) = 0\).

 

This means that \(x = \frac{-3}{2}\) and \(x = -1\)

 

- Daisy

dierdurst  Aug 27, 2018
 #1
avatar+343 
+3
Best Answer

\(2x^2 + 5x + 3 = 0\) factors to \((2x+3)(x+1) = 0\).

 

This means that \(x = \frac{-3}{2}\) and \(x = -1\)

 

- Daisy

dierdurst  Aug 27, 2018

7 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.